Remarkable intron and exon sequence conservation in human and mouse homeobox Hox 1.3 genes. - Tournier-Lasserve, E (1989)
A high degree of conservation exists between the Hox 1.3 homeobox genes of mice and humans. The two genes occupy the same relative positions in their respective Hox 1 gene clusters, they show extensive sequence similarities in their coding and noncoding portions, and both are transcribed into multiple transcripts of similar sizes. The predicted human Hox 1.3 protein differs from its murine counterpart in only 7 of 270 amino acids. The sequence similarity in the 250 base pairs upstream of the initiation codon is 98%, the similarity between the two introns, both 960 base pairs long, is 72%, and the similarity in the 3' noncoding region from termination codon to polyadenylation signal is 90%. Both mouse and human Hox 1.3 introns contain a sequence with homology to a mating-type-controlled cis element of the yeast Ty1 transposon. DNA-binding studies with a recombinant mouse Hox 1.3 protein identified two binding sites in the intron, both of which were within the region of shared homology with this Ty1 cis element.